Paroxysmal Atrial Fibrillation in Cryptogenic Stroke Patients With Major-Vessel Occlusion - Doijiri, Ryosuke; Yamagami, Hiroshi; Morimoto, Masafumi; Iwata, Tomonori; Hashimoto, Tetsuya; Sonoda, Kazutaka; Yamazaki, Hidekazu; Koge, Junpei; Kimura, Naoto; Todo, Kenichi (Frontiers in Neurology, 2020)
Background and Purpose: To determine whether acute large-vessel occlusion (LVO) predicts atrial fibrillation (AF) in cryptogenic stroke (CS) patients, we analyzed the association between acute LVO and AF detected by insertable cardiac monitoring (ICM). Methods: We conducted a retrospective, multicenter, observational study of patients with CS who underwent ICM implantation between October 2016 and March 2018. We included the follow-up data until June 2018 in this analysis. We analyzed the association of LVO with AF detected by ICM. Results: We included 84 consecutive patients with CS who underwent ICM implantation. The proportion of patients with newly detected AF by ICM was higher in patients with LVO than in those without (41% [12/29] vs 13% [7/55], p < 0.01) during within 90 days from ICM plantation. The LVO was associated with AF after adjustment for each confounding factor. Conclusions: LVO was associated with a higher risk for AF in patients with CS. Therefore, it is essential to actively assess latent AF in patients with CS presenting with LVO.